Sosialisasi Sistem QR-SAFE untuk Akses Cepat Material Safety Data Sheet (MSDS) di Industri - Tri Wahyuni Kusuma Anggun; Eka Febi Alansari; Astrid Levina Oktaviani (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The management of Material Safety Data Sheets (MSDS) at PT Phapros Tbk still faces obstacles in the form of difficult document access, numerous files scattered across several folders, and MSDS presented in English that is difficult for workers to understand. This condition has the potential to hinder understanding of chemical safety information in the work environment. This activity aims to develop a digital innovation in the form of the QR-Safe system to facilitate access and improve workers' understanding of basic MSDS information. The implementation methods include identifying problems through observation and interviews, developing a simplified MSDS summary template consisting of five main sections, creating QR codes for each chemical, and socializing the use of this innovation to employees. The results of the activity show that QR-Safe and the MSDS summary are able to speed up document searches, present safety information more concisely, and make it easier for workers to understand hazard identification, handling procedures, and the use of personal protective equipment. This innovation also contributes to improving the effectiveness of Occupational Safety and Health (OSH) in companies. The digitization of MSDS through the QR-Safe digital innovation is highly effective in improving workers' accessibility to and understanding of chemical safety information.